Research progress of cartilage lubrication and biomimetic cartilage lubrication materials - An, Haoming; Liu, Yubo; Yi, Jiafeng; Xie, Hongbin; Li, Chao; Wang, Xing; Chai, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Human joints move thousands of times a day. The articular cartilage plays a vital role in joints’ protection. If there is dysfunction in cartilage lubrication, cartilage cannot maintain its normal function. Eventually, the dysfunction may bring about osteoarthritis. Extensive researches have shown that fluid film lubrication, boundary lubrication, and hydration lubrication are three discovered lubrication models at cartilage surface, and analyzing and simulating the mechanism of cartilage lubrication is fundamental to the treatment of osteoarthritis. This essay concludes recent researches on the progress of cartilage lubrication and biomimetic cartilage, revealing the pathophysiology of cartilage lubrication and updated bio-inspired cartilage lubrication applications.